Meta-analysis of the current prevalence of screen-detected abdominal aortic aneurysm in women. Issue 9 (27th June 2016) - Ulug, P; Powell, J T; Sweeting, M J; Bown, M J; Thompson, S G; Thompson, S G; Sweeting, M J; Jones, E; Powell, J T; Ulug, P; Bown, M J; Glover, M J
Abstract: Background: Although women represent an increasing proportion of those presenting with abdominal aortic aneurysm (AAA) rupture, the current prevalence of AAA in women is unknown. The contemporary population prevalence of screen-detected AAA in women was investigated by both age and smoking status. Methods: A systematic review was undertaken of studies screening for AAA, including over 1000 women, aged at least 60 years, done since the year 2000. Studies were identified by searching MEDLINE, Embase and CENTRAL databases until 13 January 2016. Study quality was assessed using the Newcastle–Ottawa scoring system. Results: Eight studies were identified, including only three based on population registers. The largest studies were based on self-purchase of screening. Altogether 1 537 633 women were screened. Overall AAA prevalence rates were very heterogeneous, ranging from 0·37 to 1·53 per cent: pooled prevalence 0·74 (95 per cent c.i. 0·53 to 1·03) per cent. The pooled prevalence increased with both age (more than 1 per cent for women aged over 70 years) and smoking (more than 1 per cent for ever smokers and over 2 per cent in current smokers). Conclusion: The current population prevalence of screen-detected AAA in older women is subject to wide demographic variation. However, in ever smokers and those over 70 years of age, the prevalence is over 1 per cent. Abstract : Significant in older women who smoke